Modelling piezoelectric excitation in waveguides using the semi-analytical finite element method. (September 2016) - Kalkowski, Michał K.; Rustighi, Emiliano; Waters, Timothy P.
Highlights: A wave-based method for modelling piezoelectric excitation is proposed. The dynamics of the actuator and mutual actuator/structure interaction are included. The method is suitable for built-up piezo-equipped structures of an arbitrary cross-section. Very good agreement is shown in both numerical verification and experimental validation. Abstract: In this paper we present a wave-based technique for modelling waveguides equipped with piezoelectric actuators in which there is no need for common simplifications regarding their dynamic behaviour, the interaction with the waveguide or the bonding conditions. The proposed approach is based on the semi-analytical finite element (SAFE) method. We developed a new piezoelectric element and employed the analytical wave approach to model the distributed electrical excitation and scattering of the waves at discontinuities. The model was successfully verified numerically and validated against an experiment on a beam-like waveguide with emulated anechoic terminations.